Knowledge, attitude and practice of the smear test and its relation with female age - Nara Sibério Pinho Silveira; Camila Teixeira Moreira Vasconcelos; Ana Izabel Oliveira Nicolau; Mônica Oliveira Batista Oriá; Patricia Neyva da Costa Pinheiro; Ana Karina Bezerra Pinheiro (Universidade de São Paulo, 2016)
Abstract Objective: to verify the association among the knowledge attitude and practice of women in relation to the smear test and the age range. Method: a cross-sectional research was undertaken, associated with the knowledge, attitude and practice survey at a Primary Health Care service. The sample consisted of 775 women, distributed in three age ranges: adolescent, young and elderly. Results: although high rates of inappropriate knowledge were found in all age ranges, it was significantly higher among the adolescents (p=0.000). A similar trend was found in the attitude component, with percentages of inappropriateness in adolescence that drop as age advances (p=0.000). Nevertheless, no statistical difference among the groups was found in terms of practice (p=0.852). Conclusion: the study demonstrated a relation between the age range and knowledge, attitude and practice of the smear test.